ANALISA KOMPARATIF ANTARA ACUAN PERANCAH SEMI SISTEM DENGAN ACUAN PERANCAH ALUMINIUM. STUDI KASUS : PROYEK RANCANG BANGUN RUMAH SUSUN, PONDOK CINA, DEPOK - Illona Fatikah Andriyono; Agung Budi Broto (Politeknik Negeri Jakarta, 2021)
In selecting the formwork work method, the things that need to be considered include cost, quality, and time. Comparison of several methods of formwork work is carried out to obtain the correct method. Comparisons were made to the Semi System formwork method and the Aluminum formwork method. To compare the two methods requires volume calculation, the multiplier coefficient referred to by the PUPR Regulation No. 28 / PRT / M / 2016, non-conformence data, and work duration. This data is processed into the need for the cost of formwork for the two methods based on the PUPR Ministerial Regulation Number 28 / PRT / 2016, the percentage of concrete defects due to formwork, and the scheduling duration presented in the bar chart. The two methods are compared based on the need for the cost of the work, the number of percent of quality, and the work duration. The comparison shows that the aluminum formwork method is superior in terms of cost (RAB). It is produced more efficiently by 3.4%. In terms of quality, this method results in less damage (concrete defects) to minimize repair costs later, and when the work reaches 43% more effective. Keywords: Comparison, Formwork, Semi System Formwork, Aluminium Formwork.